A new arrowtooth eel of genus Meadia (Synaphobranchidae: Ilyophinae) from Vietnam, South China Sea - Vo, van Quang; Ho, Hsuan-Ching; Dao, Ha Viet; Tran, Hoa Hong Thi (Zootaxa, 2021)
Meadia minor sp. nov., a scaless ilyophine eel, is described on the basis of 10 specimens collected from off Quy Nhon, central coast of Vietnam. It can be distinguished from its congeners in having a relatively long trunk (21.3–25.0% TL) which is longer than head length; a short and blunt snout (21.4–23.7% HL); gill opening close to pectoral-fin base; interbranchial space broad (20.7–26.2% HL); dorsal-fin origin above posterior third of pectoral fin; body depth 24–28 times in TL; total vertebrae 118–122; mean vertebral formula 7-33-121; and a small body size, reaching 330 mm TL. The generic status of the new species is discussed. Short descriptions of two congeners are provided.